Comparative Analysis of Water Resources Management Service Costs for Delta Brantas Irrigation Area - Widhie Arzy Restuanti; Nadjadji Anwar; Retno Indryani (IPTEK Journal of Proceedings Series, 2017)
A proper fuction of irrigation system needs sustainable water resource management, supported by Water Resources Management Service Costs (BJPSDA). BJPSDA is a partial reimbursement of the cost required for water resource management activities, especially for operation and maintenance activities, must be calculated and set by water resources management. There are two methods that are used to calculate BJPSDA, which is BJPSDA in accordance with the Regulation of the Minister of Public Works and Public Housing No. 18/PRT/M/2015 and BJPSDA using basic service fee by considering the quality of service and value of economic benefits modelling. This study was conducted by comparing two BJPSDA methods in the Delta Brantas Irrigation Area and will be analyzed descriptively. BJPSDA of irrigation in accordance with Regulation of the Minister of Public Works and Public Housing No. 18/PRT/M/2015 is Rp. 255,-/m3, as cost recovery.. BJPSDA of irrigation value using basic service fee by considering the quality of service and value of economic benefit modelling amounted Rp. 338,-/m3, calculated from basic service fee amounted Rp. 177,-/m3, added with NME for agriculture water in Delta Brantas Irrigation Area amounted Rp. 161/m3, as a water value.